Reasons for the Failure of Web-Based Application of Information Technology Projects: An Empirical Study in Malaysia - K., Jayaraman; Hasnah, Haron; Yit, Lu Yee; Shruthi, R. (LLC “СPС “Business Perspectives”, 2015)
Every year, organizations lose millions of dollars due to failure of web-based application of information technology (IT) projects. Research shows that companies have difficulties in web-based application IT projects to complete on time or on budget or within the scope and any of these combinations. The purpose of this study is to identify the factors influencing failure of web-based application of IT projects, particularly in the context of Malaysia. The study was conducted on 155 experieced project managers in handling web-based IT projects. The top ten failure factors were identified. The findings of the study reveal that lack of clarity of goals, low teamwork quality, ineffective project management, no reward and recognition system in place and insufficient resources are the core factors for the failure of web-based application of IT projects. The significance of this research lies in the fact that its results will add new knowledge in the project management field by identifying the relative importance of the factors that have an impact on web-based application of IT project failure.